2007
DOI: 10.21273/jashs.132.2.246
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Endogenous Abscisic Acid Concentrations and Asymbiotic Seed Germination of a Terrestrial Orchid, Calanthe tricarinata Lindl.

Abstract: Changes in endogenous abscisic acid (ABA) concentrations were investigated in developing seeds and the pretreated seeds of Calanthe tricarinata, a hard-to-germinate terrestrial orchid. ABA concentration was as low as 2.16 to 2.26 ng·mg−1 fresh weight at the proembryo stage [60 to 90 days after pollination (DAP)] and then continuously increased to 11.6 ng·mg−1 fresh weight at 210 DAP. Seed maturation was accompanied by a dramatic decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 27 publications
6
39
0
2
Order By: Relevance
“…The germination frequency of fully matured seeds was much lower and only a few seeds germinated. Lee et al (2007) also noted that scarification, for example, by prolonged treatment with chemical solutions and ultrasound stimulated the germination of fully matured seeds and resulted in frequencies of seed germination (32% to 39%) similar to that of immature seeds.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…The germination frequency of fully matured seeds was much lower and only a few seeds germinated. Lee et al (2007) also noted that scarification, for example, by prolonged treatment with chemical solutions and ultrasound stimulated the germination of fully matured seeds and resulted in frequencies of seed germination (32% to 39%) similar to that of immature seeds.…”
Section: Introductionmentioning
confidence: 92%
“…Kano (1972) reported that seed germination of members of the genus Calanthe from temperate regions is the most difficult among all terrestrial species of orchid studied. There are several reports of the propagation of the genus Calanthe by the asymbiotic germination of seeds Mii 1988, 1995a, b;Fukai et al 1997;Park et al 2000;Lee et al 2007). Various strategies, such as presoaking seeds in water (Mii and Kako 1974), organic solvent (Mii 1978), phytohormones (Miyoshi and Mii 1995a), NaOCl solution (Miyoshi and Mii 1995b), and pretreatment of ultrasonication (Miyoshi and Mii 1988), and the addition of a polyphenol absorbent to the medium (Miyoshi and Mii 1995b) have been employed in efforts to improve the seed germination and/ or protocorm formation of temperate species of Calanthe.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations